(untitled) (Journal of Philosophy Culture and Political Science, 2018)
This article is devoted to the consideration of the problem of state-religion relations in modern Kazakhstan. Problems of interaction between religion and the state are considered there. Religion and State are two co-existing inalienable elements of people’s life. The author noted about its feature and roles in society and people’s life. It is shown that a close relationship and interaction of religion and state is due to the objective nature of the process of historical development. The subject for refl ection the author chose a formula that in science called the «state-religious relations.» Author tries to prove that an independent state show great responsibility and humanity by religion, choosing the only correct way in the strategic plan. The relationship of historical and cultural tradition was restored in the development of religion and the religious consciousness of the people. The authority of religion greatly increased, including Islam. It was the restoration of historical justice to the Kazakh people and their culture and religion. Constructive relationships arise between the state and religious confessions, built on the basis of: tolerance and active social and political partnership. The article defi ned its role and importance in the life of contemporary society. It is interpreted actual problems of its interaction, it is highlights the trend of this relationship now and in the future stages of development. Inter-ethnic and inter-confessional relations is one of the main lines of the new policy of the state. Today, Kazakhstan is a systematic state policy to ensure equality of citizens regardless of ethnicity or religion. There is an active involvement in their creative processes in all areas of life in the country. The Strategy «Қazahstan-2050» indicated the problems of further development of religion in Kazakhstan in XXI century. It was emphasized the preservation and strengthening of social cohesion, carried out by the state in conjunction with the Assembly of people of Kazakhstan. The religious denominations actively promoted religious revival and strengthening traditions and moral values of the Kazakhstan society. For coverage of the issue in the article uses the important documents of the Republic of Kazakhstan – Strategy «Қazahstan-2050», the 4-Congress of leaders of world and traditional religions in Astana in May 2012. Keywords: the state, Strategy, religion, state-religious relations, independence, law, interethnic and interreligious relations, tolerance, harmony, the social modernization, Congress, etc.